2012
DOI: 10.3174/ajnr.a3066
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gray Matter Atrophy in Patients with Parkinson Disease and Freezing of Gait

Abstract: BACKGROUND AND PURPOSE:FOG is a troublesome symptom of PD. Despite growing evidence suggesting that FOG in PD may be associated with cognitive dysfunction, the relationship between regional brain atrophy and FOG has been poorly investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
71
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 42 publications
16
71
2
Order By: Relevance
“…2) The cerebral cortex seems to modify the relation between the cycle and the force, formulated in the basal ganglia, depending on the context in which walking movements are performed. This idea is in good agreement with the recent findings revealed by new imaging techniques [30][31][32]. These studies showed that white matter lesions disrupted balance/locomotor circuits and thereby caused the highlevel gait disorders characterized by deficits in strength, tone, sensation or coordination.…”
Section: How Is the Gait Strategy Selected By Neural Circuitry?supporting
confidence: 80%
“…2) The cerebral cortex seems to modify the relation between the cycle and the force, formulated in the basal ganglia, depending on the context in which walking movements are performed. This idea is in good agreement with the recent findings revealed by new imaging techniques [30][31][32]. These studies showed that white matter lesions disrupted balance/locomotor circuits and thereby caused the highlevel gait disorders characterized by deficits in strength, tone, sensation or coordination.…”
Section: How Is the Gait Strategy Selected By Neural Circuitry?supporting
confidence: 80%
“…10 In addition, some studies have failed to find any GM change. [11][12][13][14] In fact, few of these previous findings were wholly consistent with each other. These inconsistencies may result from the patient heterogeneity, such as the age, disease duration, disease severity, and variable covariates used in VBM analysis, which may confound the effect of results in between-group differences.…”
mentioning
confidence: 64%
“…5 ) did not reveal any regional cortical atrophy specific for FOG on the whole-brain level, but described local GM atrophy in a small portion of the mesencephalic locomotor region (MLR) along with functional hyperactivation during walking imagery 5 . In contrast, when Tessitore et al 6 directly contrasted PD patients with and without FOG, they found GM atrophy in the left cuneus, lingual gyrus, precuneus, and posterior cingulate cortex. On the other hand, when comparing GM atrophy in PD patients with FOG to both control subjects and PD patients with no FOG, Kostic et al 7 observed atrophy of the left inferior frontal gyrus, left precentral gyrus, and left inferior parietal gyrus.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we used the FreeSurfer implementation of surfacebased analysis and our results demonstrate that patients with FOG exhibited atrophy of the bilateral cingulate cortex (mostly in mid-anterior part), left supplementary motor area (SMA), and right frontal operculum. In summary, earlier publications reported rather complex pattern of functional and morphological changes [6][7][8][9][10][11]29 , suggesting a complex pathophysiological substrate of FOG. Whereas the automatic control of gait appears to be subserved by brainstem nuclei and their corresponding circuits, involvement of cortical brain structures is presumed in FOG because of frequent manifestation of freezing in situations with emotional or cognitive context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation